Single-step separation scheme and high-precision isotopic ratios analysis of Sr–Nd–Hf in silicate materials - Li, C.; Guo, J.; Yang, Y.; Chu, Z.; Wang, Xuan-Ce (Royal Society of Chemistry, 2014)
Thermal ionization mass spectrometry and multiple-collector inductively coupled plasma mass spectrometry are considered to be “gold standards” for the determination of the isotope ratios of Sr–Nd and Hf in geological samples because of the extremely high precision and accuracy of these methods. However, the sample throughputs are hindered by time-consuming and tedious chemical procedures. Three-step ion exchange resin separation is traditionally employed to purify Sr–Nd–Hf from matrix elements. In this study, a one-step Sr–Nd–Hf separation scheme was developed to process geological samples. The separation scheme is based on the combined use of conventional AG50W-X12 cation-exchange resin and LN Spec extraction chromatographic material without any intervening evaporation step. The protocol not only prevents cross-contamination during operation using multiple-stage ion exchange resins but also significantly improves the efficiency of sample preparation. The stability of our chemical procedure was demonstrated by replicate measurements of 87Sr/86Sr, 143Nd/144Nd, and 176Hf/177Hf ratios in six international reference materials of silicate rocks. The analytical results obtained for these standard rocks compare well with the published data. The external reproducibility (2 SD, n = 10) of a BCR-2 standard sample was ±0.000018 for 87Sr/86Sr, ±0.000010 for 143Nd/144Nd, and ±0.000014 for 176Hf/177Hf.